Influence of Texture on the Mechanical Properties of a Mg-6Al-1Zn-0.9Sn Alloy Processed by ECAP - Xu, Hong (Materials (Basel), 2021)
The microstructure and mechanical properties of a Mg-6Al-1Zn-0.9Sn alloy processed by equal channel angular pressing (ECAP) at temperatures of 250 °C and 300 °C were investigated. It was found that the refinement of the microstructure was very dependent on the processing temperature. The main reason for the difference in grain refinement was the precipitation of secondary-phase particles. Texture information obtained by electron back-scatter diffraction (EBSD) showed the gradual formation of a 45° texture during the ECAP process, while the maximum intensity was different for processing temperatures at 250 °C and 300 °C. By calculating the contribution from different strengthening mechanisms, it was found that a 45° texture had a huge influence on grain boundary strengthening and thus the yield strength.